Inclusive marketing a trend in the market to explore: La Favorita case - Lemache Cueva, Nayomi; Cueva Murillo, María Eugenia; Erique Pereira, Francisco (mktDESCUBRE, 2021)
The purpose of this article is to analyze the ambivalence that exists between the corporate image and identity of Corporación La Favorita C.A. against minority and historically excluded groups such as LGBTIQ + people in the use of digital marketing strategies in June for the commemoration of the so-called “Pride Month”. The research is explanatory, which will allow the analysis and synthesis of conceptualizations, differentiations and substantial considerations of inclusive and diverse marketing in the Ecuadorian business field. As a result, the scarce visibility and transcendence that gender diversity groups have in the planning, elaboration and distribution of digital content is exposed, leaving as the main conclusion the existing roots towards a traditional marketing style based on the permanence of Eurocentric roles and stereotypes. In addition, it reveals the little interest that the economic group has to exploit a market that worldwide, especially in Latin America, has had a positive impact, generating greater profitability, loyalty and equality through the deployment of communication practices in favor of the inclusive and diverse.